Impact of microwave pulses of ultrashort duration on a personal computer - Gadetski, N.P.; Karelin, S.Yu.; Magda, I.I.; Shapoval, I.M.; Soshenko, V.A. (Вопросы атомной науки и техники, 2017)
Procedure of the tests for electromagnetic compatibility and strength (EMSS) of a personal computer (PC) to microwave ultrashort duration pulse (USP) and analysis of the results are described. 3D simulation of the MW USP interaction with the test objects considering the configuration of the test area and screening effect of metal components estimates the level of electromagnetic field inside the PC case. Numerically and experimentally is shown that the MW field penetrating into the metal PC case through technological holes can induce the USP potentials in the PC circuitry sufficient to create functional upsets and degradations.